Pemodelan Pemilihan Lokasi Pembuangan Sampah Akhir pada Dinas Lingkungan Hidup Kota Yogyakarta - Mukh. Nasir Ramdhani; Prita Meilanitasari (OPSI, 2019)
Population growth rate and urban lifestyle have an impact on increasing the volume of waste. The problem is related to the concept of Municipal Waste Collection (MWC) for waste management. Waste management considers transportation and distribution from the Temporary Disposal Site (TPS) to the location of the Final Disposal Site (TPA). Routing and allocation for waste disposal in the urban area gave a big concern for the society. This study will raise the issue of allocation, distribution and transportation to support overall waste management in urban areas. This study will use Integer Linear Programming approach for modeling the selection of the final location of TPA by considering the distance from each TPS to the TPA. This study also considers the conversion value of the weight of municipal solid waste in Yogyakarta City. In the practice, Yogyakarta City has 1 TPA with 73 TPS. Authors generate 1 new TPA as an alternative. This study will give an alternative allocation, distribution and transportation from each TPS which optimized the capacity of TPA.